The Development of Website-Based Training Program Planning - Ibrahim Ibrahim; Syahputra Manik; Indra Kasih (Budapest International Research and Critics University, 2022)
The purpose of this research is to create a sports training program planning website so that it can make it easier for sports coaches to make training programs in a structured and systematic manner. In addition, this website is also a media for students to improve their abilities in making and planning sports training programs, so that FIK Unimed graduates can compete in the world of coaching, especially in North Sumatra. The research method used is research and development (R&D) by design development research proposed by; Borg and Gall, This research and development uses a qualitative approach and uses research & development (R & D) research methods. The instruments used in this research and development are a). Examine the experts (expert judgment). Validation from material experts shows an assessment result of 83% which means that website development is feasible. Meanwhile, media experts showed an assessment result of 81.25%. In the small group trial, as many as 80% of respondents answered the range of values between 80-100% which was included in the feasible category.